“Let You Have Nine Sons and One Daughter”: Naming a Young Man and a Girl in the Veps Ethnolinguistic Space - N. G. Zaitseva; O. Yu. Zhukova (Научный диалог, 2020)
The results of a comparative analysis of the vocabulary of a thematic group of Vepsian-speaking naming concepts of “boy” and “girl” are presented in the article. The authors believe that it is the historical realities of life and the special position of males in the Russian state, primarily associated with the allotment of land, reflected in the formation of vocabulary of the Veps language of this group. The question is raised about the Vepsian special desire to present and embody in language images certain complete, terminological, correspondences to Russian naming, which initiated the appearance of borrowings from the Russian language and Russian dialects. Attention is drawn to the studies of etymologists regarding the lexeme denoting a boy, a young man, which is considered to be Russian borrowing in the Veps and Karelian languages: Veps. priha Kar. Briha